2022
DOI: 10.20892/j.issn.2095-3941.2022.0049
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting pyroptosis to fuel cancer immunotherapy: mechanisms and strategies

Abstract: Immune checkpoint blockade (ICB) therapy has recently shown promise in treating several malignancies. However, only a limited number of patients respond to this treatment, partially because of the “immune cold” condition of the tumor immune microenvironment. Pyroptosis is a type of gasdermin-mediated programmed cell death that often leads to inflammation and immune responses. Many studies on the mechanism and function of pyroptosis have led to increasing recognition of the role of pyroptosis in malignant progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 124 publications
0
11
0
Order By: Relevance
“…Similar to other forms of cell death like ferroptosis and pyroptosis, cuproptosis has been found to contribute to tumor immunogenicity, harboring the potential to enhance the effectiveness of immune checkpoint therapy (ICB). Tumor immunotherapy based on ICB has emerged as a pivotal approach for combating cancer by augmenting and activating the body’s immune responses . As a compelling alternative to chemotherapy, radiotherapy, and targeted therapy, it has demonstrated substantial clinical efficacy and notable advantages. , Even before the discovery of cuproptosis, researchers have demonstrated that copper levels within tumors affect the expression of PD-L1 in cancer cells . Therefore, there is a potential synergistic effect between cuprotosis and ICB therapy.…”
Section: Targeting Cuproptosis: Shooting a Nanodrug Into Achilles’ Heelmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to other forms of cell death like ferroptosis and pyroptosis, cuproptosis has been found to contribute to tumor immunogenicity, harboring the potential to enhance the effectiveness of immune checkpoint therapy (ICB). Tumor immunotherapy based on ICB has emerged as a pivotal approach for combating cancer by augmenting and activating the body’s immune responses . As a compelling alternative to chemotherapy, radiotherapy, and targeted therapy, it has demonstrated substantial clinical efficacy and notable advantages. , Even before the discovery of cuproptosis, researchers have demonstrated that copper levels within tumors affect the expression of PD-L1 in cancer cells . Therefore, there is a potential synergistic effect between cuprotosis and ICB therapy.…”
Section: Targeting Cuproptosis: Shooting a Nanodrug Into Achilles’ Heelmentioning
confidence: 99%
“…165 As a compelling alternative to chemotherapy, radiotherapy, and targeted therapy, it has demonstrated substantial clinical efficacy and notable advantages. 164,166 Even before the discovery of cuproptosis, researchers have demonstrated that copper levels within tumors affect the expression of PD-L1 in cancer cells. 167 Therefore, there is a potential synergistic effect between cuprotosis and ICB therapy.…”
Section: Targeting Cuproptosis: Shooting a Nanodrug Into Achilles' Heelmentioning
confidence: 99%
“…[141,142] This process enhances the activity of tumor infiltration lymphocytes, such as natural killer (NK) cells, CD4 + T cells, and dendritic cells (DCs), thereby stimulating the maturation of IL-18 and IL-1𝛽 to activate anti-tumor immune responses. [128,143,144] Thus, the use of nanomaterials to induce pyroptosis offers a wide range of potentials for improving tumor immunotherapy. [145] For example, Ding et al developed biodegradable K 3 ZrF 7 : Yb/Er upconversion nanoparticles (ZrNPs), which could induce pyroptosis by releasing large amounts of K + and [ZrF 7 ] 3− ions to activate superior antitumor immunity (Figure 7A).…”
Section: Pyroptosis Activation Via the Canonical Pathway-enhanced Imm...mentioning
confidence: 99%
“…Ferroptosis is immunogenic in vitro and in vivo 5 . The immune system has a substantial role in exerting antitumor immunity; however, tumor cells have developed multiple ways to escape immune surveillance, including reducing immunogenicity and forming immunosuppressive networks, rendering tumor immunotherapy clinically inefficient 6 . Therefore, inducing ferroptosis in tumor cells stimulates the immune system and enhances the efficacy of immunotherapy.…”
Section: Remodeling Of the Tumor Microenvironment After Triggering Fe...mentioning
confidence: 99%